2017
DOI: 10.1186/s12931-017-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of breath test for pneumoconiosis: a case-control study

Abstract: BackgroundLipid peroxidation plays an important role in the pathogenesis of pneumoconiosis. Volatile organic compounds (VOCs) generated from lipid peroxidation might be used to detect pneumoconiosis. The objective of this study was to develop a breath test for pneumoconiosis.MethodsA case-control study was designed. Breath and ambient air were analysed by gas chromatography/mass spectrometry. After blank correction to prevent contamination from ambient air, we used canonical discriminant analysis (CDA) to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Lawal et al [ 52 ] studied VOC signatures from volatile emissions derived from the co-culture of lung epithelial cell line with bacterial pathogen Pseudomonas aeruginosa and found several alkanes associated with immune responses. Yang et al [ 53 ] found that lipid peroxidation-induced pentane and C5–C7 methylated alkanes constituted a specific fingerprint in the breath of pneumoconiosis patients. If induction of alkane emissions as an indicator of immune operation applies to similar physiological activities in Pd-infected bats, the higher emissions of methylated and ethylated alkanes in active bats might provide a chemical indicator of greater immune activity operating in healthy field bats than are measured in torpid WNS-diseased bats with altered immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Lawal et al [ 52 ] studied VOC signatures from volatile emissions derived from the co-culture of lung epithelial cell line with bacterial pathogen Pseudomonas aeruginosa and found several alkanes associated with immune responses. Yang et al [ 53 ] found that lipid peroxidation-induced pentane and C5–C7 methylated alkanes constituted a specific fingerprint in the breath of pneumoconiosis patients. If induction of alkane emissions as an indicator of immune operation applies to similar physiological activities in Pd-infected bats, the higher emissions of methylated and ethylated alkanes in active bats might provide a chemical indicator of greater immune activity operating in healthy field bats than are measured in torpid WNS-diseased bats with altered immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to metal canisters, glass containers have been used for sampling breath [6]. Despite their fragility, they can be more performant than Tedlar bags as reporter by Scott-Thomas et al [7].…”
Section: Canistersmentioning
confidence: 99%
“…The high-speed MS detector time of flight (TOF) is often used as a detector for the GC × GC. Using MS with GC × GC separation (6) to detector (7). With permission from [35].…”
Section: Principlementioning
confidence: 99%
“…Exhaled breath VOCs have been utilised in various other respiratory illnesses, nearly 90% of 25 patients with Pneumoconiosis were discriminated by their breath profile (ROC-AUC 0.88) 93 .…”
Section: Vocs In Other Respiratory Conditionsmentioning
confidence: 99%